REINKARNASI POLITISI BERTABUR BINTANG PASCA REFORMASI - Andi Ali Said Akbar (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Although trauma and public skepticism toward the military is still quite strong; though the sins of the military during the New Order freely beragai stripped naked in public space during the reform. In fact, military figures rose even more flying in many national level either party until the local level, both old and new parties. To face the new system of political contestation and the military is benefiting from a weakening factor of the consolidation of civilian political forces. Political parties and civic leaders increasingly anti Orba number berjibun be a dilemma. Elections are approaching need fresh energy to be the winner while they are still haunted by the various limitations of the cadre of crisis, financial crisis and the crisis of political networks. To rise, the former general has a genetic modalities required political parties and civic leaders that organizational discipline, a network of territorial and political violence. Political modalities of military culture is that interest civilian politicians because it can be replicated in consolidating the power of the party, although very risky memangun consolidation of democracy in Indonesia in the future. The choices here are to be assessed for reading the direction of the democratization of Indonesia.